Evaluating the tangible, acknowledging the intangible : the application of auditing, kaitiakitanga and collection management during the Tairāwhiti museum taonga Māori audit : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University, Manawatu, New Zealand - Colmer, Paki-Moana (Massey University, 2010)
The objective of this dissertation is to reveal how the application of auditing and holistic collection management practices can bring about tangible and mutually beneficial outcomes for museums, Māori and taonga Māori collections. The core research of this dissertation is a case study of the Tairāwhiti Museum Taonga Māori Audit. This demonstrates the praxis of auditing; the concurrent application of kaitiakitanga and collection management principles; and the strategic outcomes that may be achieved when undertaking similar initiatives. At present the practice and implications of auditing for museums is an underdeveloped area of enquiry. This dissertation clarifies auditing and its emergence in museum practice; the current debates surrounding it; and examples of national and international auditing to place the Tairāwhiti Museum Audit within the broader context of museum based auditing. The Tairāwhiti Museum Audit demonstrates the rationale, implementation and potential benefits of auditing as a strategic collection management tool. To provide an epistemological framework for the Tairāwhiti Museum Audit the context of taonga Māori from the Māori worldview is clarified, and an overview of shifts toward the acknowledgement and application of mātauranga Māori principles in New Zealand museums is provided. The approach of the Tairāwhiti Museum toward the collection management of taonga has been influenced by external shifts, but more often has been progressive in its response toward meeting the expectations of local Māori and the needs of the taonga Māori collection. The Tairāwhiti Museum Audit is further evidence of this. The dissertation reveals the relevance of taonga to Māori, and demonstrates how kaitiakitanga principles can be applied to strategic collection management initiatives.
Keywords: Museum auditing; Maori antiquities; Cultural property; Museum management